ByzRev 06.2024.059: Émeline Marquis (Hrsg.), Epistolary Fiction in Ancient Greek Literature: (Philologus. Supplemente / Philologus. Supplementary volumes 19). Berlin – Boston: De Gruyter 2023. - Grünbart, Michael (The Byzantine Review, 2024)
Émeline Marquis (Hrsg.), Epistolary Fiction in Ancient Greek Literature (Philologus. Supplemente / Philologus. Supplementary volumes 19). Berlin – Boston: De Gruyter 2023. VIII, 243 S. – ISBN 978-3-11-099624-1